Characterization of HVPE‐grown UV LED heterostructures. Issue 3 (5th March 2014) - Kurin, Sergey; Antipov, Andrey; Barash, Iosif; Roenkov, Alexander; Usikov, Alexander; Helava, Heikki; Ratnikov, Valentin; Shmidt, Natalia; Sakharov, Alexey; Tarasov, Sergey; Menkovich, Ekaterina; Lamkin, Ivan; et al.
Abstract: In this paper, we report on growth of ultraviolet light‐emitting diode (UV LED) heterostructures by hydride vapour phase epitaxy (HVPE) on sapphire substrates and results of the heterostructures characterization by X‐ray diffractometry, scanning electron microscopy, photo‐ and electroluminescence, micro‐photoluminescence, collected from the cleaved edges and the surface of the heterostructure with lateral resolution of about 1 µm. The heterostructures demonstrate efficient hole injection and low droop of the external quantum efficiency. Packaged 360 nm UV LED chips have wall‐plug efficiency of 1‐1.5%. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)